OLAHRAGA BERSEPEDA SEBAGAI PILIHAN RASIONAL DI MASA PANDEMI COVID-19 - Sebayang, Oky Peramana; Nugroho, Wahyu Budi; Krisna Aditya, I Gusti Ngurah Agung (JURNAL ILMIAH SOSIOLOGI: SOROT, 2021)
The COVID-19 pandemic has raised public awareness of the importance of health. This is evidenced by the emergence of cycling trends during the Covid-19 pandemic, cycling is considered safe and implementing elements of health protocols, namely maintaining distance and without physical contact. This study aims to describe and explain why people choose cycling as a rational choice of sport during the Denpasar City pandemic and how its social impact is. The theory used in this research is James S Coleman's rational choice theory. The results of the field research show that considerations of costs, benefits, risk of infection and limited options are the basis for people to choose cycling and other factors are friends and social media. The positive social impact is new friends, new knowledge and increased enthusiasm for sports, the negative impact is population density and there are still many cyclists who do not obey the rules on the road. Keywords: cycling, Covid-19, rational choice